THE EFFECT OF DEBT TO EQUITY RATIO AND RETURN ON EQUITY ON STOCK RETURN WITH DIVIDEND POLICY AS INTERVENING VARIABLES IN SUBSECTORS PROPERTY AND REAL ESTATE ON BEI - Dina Nurhikmawaty; Isnurhadi Isnurhadi; Marlina Widiyanti; Yuliani Yuliani (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
ABSTRACTDebt to Equity Ratio (DER) and Return on Equity (ROE) to stock returns with dividend policy as an intervening variable on property and real estate companies listed on the Indonesia Stock Exchange in 2014-2018. This type of research is quantitative. This research population publishes all property and real estate companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling. The data contributed to the research of 54 companies, and obtained a sample of 18 companies. Data analysis method used is path analysis (path analysis) using the multiple test. Based on the results of data analysis, it shows that: (1) Debt to Equity Ratio (DER) does not affect stock returns; (2) Return on equity (ROE) has a significant effect on stock returns; (3) Debt to Equity Ratio (DER) has a significant effect on Dividend Payout Ratio (DPR); (4) Return on equity (ROE) has a significant effect on Dividend Payout Ratio (DPR); (5) Dividend Payout ratio (DPR) can mediate the effect of Debt to Equity Ratio (DER) on stock returns; (6) Dividend payout ratio (DPR) can mediate the effect of return on equity (ROE) on stock returns.Keywords:Debt to Equity Ratio (DER), Return on equity (ROE), Stock Returns, Dividend Payout Ratio (DPR), Dividend Policy